2011
DOI: 10.2310/jim.0b013e31822cf97a
|View full text |Cite
|
Sign up to set email alerts
|

P-Wave Duration and Dispersion in Patients with Emery-Dreifuss Muscular Dystrophy

Abstract: Our study showed a significant increase of maximum P-wave duration and PD in patients with EDMD with conserved systolic and diastolic cardiac function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 31 publications
0
17
0
Order By: Relevance
“…PD has been studied in some other conditions such as hypertension [29], obesity [30], diabetes mellitus [31], metabolic syndrome [32], dilated cardiomyopathy [33], myocardial infarction [34], atrial septal defect [35], hypertrophic cardiomyopathy [36], obstructive sleep apnea [37], Emery Dreifuss muscular dystrophy [38] and Wilson's disease [39]. The exact mechanism of PD prolongation in these clinical conditions is not well known, but it is thought that structural and electrophysiological changes in the atrial myocardium caused by elevated plasma volume [40], ventricular diastolic dysfunction [41] and enhanced neurohormonal activation [42], typical conditions of these deseases, may contribute to left atrial enlargement and electrical instability.…”
Section: Discussionmentioning
confidence: 99%
“…PD has been studied in some other conditions such as hypertension [29], obesity [30], diabetes mellitus [31], metabolic syndrome [32], dilated cardiomyopathy [33], myocardial infarction [34], atrial septal defect [35], hypertrophic cardiomyopathy [36], obstructive sleep apnea [37], Emery Dreifuss muscular dystrophy [38] and Wilson's disease [39]. The exact mechanism of PD prolongation in these clinical conditions is not well known, but it is thought that structural and electrophysiological changes in the atrial myocardium caused by elevated plasma volume [40], ventricular diastolic dysfunction [41] and enhanced neurohormonal activation [42], typical conditions of these deseases, may contribute to left atrial enlargement and electrical instability.…”
Section: Discussionmentioning
confidence: 99%
“…56 The identification of b-TM patients with atrial fibrillation risk is of pivotal importance for the optimization of the medical therapy to prevent tromboembolic stroke. [59][60][61] In our previous studies, 62,63 we showed a significant increase in P wave dispersion, correlated with myocardial iron deposit, assessed by Cardiac Magnetic Resonance (CMR) T2 imaging, in b-TM patients with conserved systolic and diastolic cardiac function and we suggested the hypothesis that the abnormal P wave dispersion ≥35.5 ms and maximum P wave duration ≥111 ms may predict atrial fibrillation onset in beta thalassemia major patients, even when the cardiac function is conserved. 57 PD was shown to be an independent risk factor for the development of atrial fibrillation.…”
Section: Atrial Fibrillationmentioning
confidence: 99%
“…58 It has been studied in some clinical conditions. [59][60][61] In our previous studies, 62,63 we showed a significant increase in P wave dispersion, correlated with myocardial iron deposit, assessed by Cardiac Magnetic Resonance (CMR) T2 imaging, in b-TM patients with conserved systolic and diastolic cardiac function and we suggested the hypothesis that the abnormal P wave dispersion ≥35.5 ms and maximum P wave duration ≥111 ms may predict atrial fibrillation onset in beta thalassemia major patients, even when the cardiac function is conserved. For b-TM patients with atrial fibrillation onset high risk, we suggest a careful cardiac monitoring with seriate ECG Holter monitoring or cardiac loop ECG recordings, to early detect atrial fibrillation onset and to evaluate the opportunity of prophylactic anticoagulation treatment.…”
Section: Atrial Fibrillationmentioning
confidence: 99%
“…Noninvasive electrocardiographic and echocardiographic markers are useful in clinical practice to predict arrhythmias in some clinical conditions, [6][7][8][9][10] including muscular dystrophy. [11][12][13][14][15] In particular, we previously showed that the electrocardiographic (P-wave duration and dispersion) and echocardiographic noninvasive indicators of atrial conduction heterogeneity (intraleft and interatrial electromechanical delay indices) were significantly increased in DM1 patients with AF compared to those with no arrhythmias and were independent predictors of AF onset. 4,14 Therefore, we suggest the authors to include in their future analysis a detailed evaluation about the clinical utility of these electrocardiographic and echocardiographic parameters for predicting supraventricular and ventricular arrhythmias in DM1 population.…”
Section: Which Is the True Epidemiology Of Atrial Fibrillation In Myomentioning
confidence: 99%
“…For the high supraventricular arrhythmias risk and its consequences, the early identification of DM1 patients with atrial fibrillation risk is of pivotal importance for the optimization of the clinical follow‐up and medical therapy. Noninvasive electrocardiographic and echocardiographic markers are useful in clinical practice to predict arrhythmias in some clinical conditions, including muscular dystrophy . In particular, we previously showed that the electrocardiographic (P‐wave duration and dispersion) and echocardiographic noninvasive indicators of atrial conduction heterogeneity (intraleft and interatrial electromechanical delay indices) were significantly increased in DM1 patients with AF compared to those with no arrhythmias and were independent predictors of AF onset .…”
mentioning
confidence: 99%